A Reader's Guide to Wallace Stevens - Cook, Eleanor (Book collections on Project MUSE., 2009)
Wallace Stevens is one of the major poets of the twentieth century, and also among the most challenging. His poems can be dazzling in their verbal brilliance. They are often shot through with lavish imagery and wit, informed by a lawyer's logic, and disarmingly unexpected: a singing jackrabbit, the seductive Nanzia Nunzio. They also spoke--and still speak--to contemporary concerns. Though his work is popular and his readership continues to grow, many readers encountering it are baffled by such rich and strange poetry. Eleanor Cook, a leading critic of poetry and expert on Stevens, gives us her.